Agroclimatic zoning for urucum crops in the state of Minas Gerais, Brazil - Oliveira Aparecido, Lucas Eduardo de [UNESP]; Rolim, Glauco de Souza [UNESP]; Silva Cabral de Moraes, Jose Reinaldo da [UNESP]; Rocha, Helio Gallo [UNESP]; Expedito Lense, Guilherme Henrique [UNESP]; Souza, Paulo Sergio [UNESP] (Inst Agronomico, 2018)
Hardier crops are needed in the arid regions of the Brazilian state of Minas Gerais, and annatto (Bixa orellana L.) is a good candidate. Producers, however, do not know if their areas are suitable for its cultivation and so are not investing in its implementation. Agroclimatic zoning would provide guidance to the producers. Identifying potential areas for the production of this crop would thus contribute to the agroclimatic zoning of B. orellana in Minas Gerais. We collected data for air temperature and precipitation from 852 meteorological stations in the state to classify regions as suitable, marginally suitable, or unsuitable for the crop. Suitable regions had an air temperature between 22 and 27 degrees C and precipitation between 800 and 1600 mm.y(-1). Marginally suitable regions had an air temperature between 22 and 27 degrees C and precipitation less than 800 mm.y(-1). Unsuitable regions had air temperature less than 22 degrees C or greater than 27 degrees C. A geographic information system was used for the spatial interpolation of air temperature and precipitation for all meteorological stations using kriging. The agroclimatic zoning of annatto crops for Minas Gerais was obtained by interpolating the two maps, air temperature and precipitation. Minas Gerais has great potential for urucum production, and agroclimatic zoning enabled the classification of regions by climatic suitability. The northern, western, northwestern, and part of the eastern regions of Minas Gerais have favourable climates suitable for the cultivation of B. orellana.
Keywords: climatic risk; climatic modeling; agrometeorology; Bixa orellana L.